Conceptualising scholarship within college-based higher education. Issue 1 (9th February 2015) - Eaton, Jonathan
Abstract : Purpose: – During a period of significant crisis within HE on a global scale, there is a clear need for colleges to clearly articulate the distinct nature of their higher vocational education provision. This need is particularly acute given the current financial and political pressures impacting on a diverse HE landscape. The purpose of this paper is to argue that colleges are well placed to develop and implement an approach to scholarly activity which revitalises links with local communities. Design/methodology/approach: – This paper provides a synthesis of recent research on scholarly activity within college-based higher education (CBHE) and the concept of a "civic university". It also provides a brief case study of how scholarship within the college context can be utilised to promote meaningful community engagement. Findings: – Working productively with community organisations, groups and individuals, colleges will be provoked to recast the complex relationship between teaching, research and community engagement in a manner appropriate to their immediate context rather than a national agenda. Moreover, a strengthened relationship between colleges and their local communities will recapture the rich heritage of vocational education in widening participation and raising aspirations towards education in general. Originality/value: – This paper attempts to relocate current discussions of CBHE scholarly activity within the context of civic engagement. It will be of interest to colleagues across the higher vocational education sector, both nationally and internationally, in situating their institutional and departmental scholarly activity strategies within the context of the communities which they serve.